Effect of Conjugated Linoleic Acid on Memory and Reflex Maturation in Rats Treated During Early Life - Queiroz, Michelly Pires; Lima, Martiniano da Silva; Barbosa, Mayara Queiroga; Melo, Marilia Ferreira Frazão Tavares de; Bertozzo, Camila Carolina de Menezes Santos; Oliveira, Maria Elieidy Gomes de; Bessa, Rui José Branquinho; Alves, Susana Paula Almeida; Souza, Maria Izabel Amaral; Queiroga, Rita de Cassia Ramos do Egypto; Soares, Juliana Késsia Barbosa (Frontiers in Neuroscience, 2019)
In the critical period of neurodevelopment (gestation and lactation), maternal consumption of essential fatty acids can alter the offspring cognitive function permanently causing damage. Lipids can regulate neurotrophin and compose brain tissue. However, the effects of maternal consumption of a mixture of conjugated linoleic acid (CLA) on an offspring nervous system are not completely clear. We aimed to investigate the impacts of different CLA concentrations mixed into the maternal diet during early life on neonatal reflex maturation and cognitive functions of the offspring. Three groups were formed: control (CG): receiving a standard diet; CLA1: receiving a diet containing 1% of CLA, and CLA3: receiving a diet containing 3% of CLA, offered during gestation and lactation. After birth, the reflex responses of the offspring were observed from the 1st to the 21st day. After weaning, the animals’ anxiety and memory were assessed using Open Field (OF) and Novel Object Recognition tests. Fatty acids in the breast milk and the offspring’s brain were also quantified. The data were analyzed using one-way ANOVA and the Kruskal–Wallis test. CLA1 presented accelerated palmar grasp disappearance versus CLA3 and negative-geotaxis versus CG; and the CLA3 presented increases for most reflexes (cliff-avoidance, vibrissa-placing, negative-geotaxis and auditory-startle response), and decrease in reflexes palmar grasp and free-fall righting versus CG (p<0.05). CLA3 group explored less of the OF in the second exposure. CLA1 and CLA3 presented an increased exploration ratio for new objects, which indicates memory improvement. The milk tested from CLA3 demonstrated an increase in polyunsaturated fatty acids (PUFA), and a decrease in monounsaturated fatty acids (MUFA). The amount of CLA in milk was greater in CLA1 and CLA3 and in the brain offspring both presented moderated amounts of CLA. Maternal treatment with the CLA mixture induced anticipated reflex maturation and improved memory in the offspring. Even though CLA was detected in the brains in only trace amounts, offspring’s brain PUFA and SFA levels were increased. Further studies aimed to delineate the effect of maternal CLA supplementation on offspring’s brain lipid metabolism and long-term neurologic outcome are needed to confirm these findings.